PENGARUH MODEL MASTERY LEARNING MENGGUNAKAN MEDIA GAMBAR SERI TERHADAP KEMAMPUAN MENULIS KARANGAN PESERTA DIDIK MADRASAH IBTIDAIYAH - Hamidah, Allinda; Artini, Artini (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The mastery learning model using Image Series media is a learning process by fully mastering the material assisted by media, namely a series of images. This research aims to determine the effect of the mastery learning model using a series of image media on the essay writing ability of Class IV students at the Miftahul Ulum Banjarejo Lamongan Elementary School. This type of research is quantitative using a pre-experimental design method type one group pretest-posttest (initial test – single group final test). The data collection methods used are observation, testing, and documentation. The data analysis techniques used are descriptive analysis, normality testing and hypothesis testing. The results of the research show that the application of the Mastery Learning model using a series of image media averages 82% in the very good category. The students' essay writing ability obtained in the pre-test got an average score of 57.28 in the sufficient category in the range of 40- 60, while the post-test got an average score of 82.71 in the very good category in the 80-100 range. The results of the normality test analysis with the help of SPSS and the results of the significance value are 0.010 > 0.05, it can be concluded that the residual values ​​are normally distributed. followed by hypothesis testing, namely by using a simple linear regression test with the help of SPSS with the provisions Sig < α, namely 0.000 < 0.05 and count < ttable, namely 7,468 > 0.444, which means that Ha is accepted and Ho is rejected, so there is an influence of using the mastery learning model using series image media. on the ability to write Indonesian essays for class IV students. By carrying out this research, it is hoped that teachers can create interesting variations of learning in the classroom with the hope that learning activities can be more enjoyable, and students will be more active so that students' ability to write Indonesian essays will increase.